Cyclical and structural determinants of involuntary part-time employment in Turkey - ERİŞ DERELİ, BİLGE; DÜZGÜN ÖNCEL, BURCU (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
We examine the correlates of involuntary part-time employment in Turkey. We contribute to previous studies regarding Turkey on two aspects. First, we focus on the cyclical and structural components that capture both labour demand and supply conditions, respectively. Second, we control for sample selection bias by applying a recursive bivariate model. We find that involuntary part-time employment is more common among males and moves with unemployment rate. Estimation results present a strong association between involuntary part-time employment and structural factors.
Keywords: Involuntary part-time employment; Turkey; household labour surveys; recursive bivariate model